ผลการใช้รูปแบบการจัดการสารสนเทศการเกษตรสู่เกษตรกร กรณีศึกษาเกษตรกรที่เพาะปลูกข้าว - รื่นรมย์, อรวดี; วิรุณราช, บรรพต (วารสารวิทยบริการ มหาวิทยาลัยสงขลานครินทร์ | Academic Services Journal, Prince of Songkla University; Vol 30 No 1 (2562): Academic Services Journal, Prince of Songkla UniversityDO - 10.14456/asj-psu.2019.11, 2019)
การวิจัยครั้งนี้มีวิธีดำเนินการวิจัยเชิงปฏิบัติการ มีวัตถุประสงค์เพื่อศึกษาผลการใช้รูปแบบการจัดการสารสนเทศการเกษตร และหาแนวทางการพัฒนารูปแบบการจัดการสารสนเทศเพื่อส่งต่อสู่เกษตรกรนำไปใช้ประโยชน์ โดยผู้วิจัยดำเนินการตามรูปแบบการจัดการสารสนเทศที่ได้ออกแบบ และทำหน้าที่เสมือนศูนย์ประมวลข้อมูลเพื่อดำเนินการรวบรวมข้อมูลการเกษตรเป็นรายสัปดาห์จากทุกภาคส่วน หลังจากนั้นนำมาประมวลโดยผ่านกระบวนการวิเคราะห์สังเคราะห์ให้เป็นสารสนเทศการเกษตร 6 ประการ ได้แก่ 1) สภาพแวดล้อมที่มีผลต่อการเพาะปลูก 2) นโยบายภาครัฐ 3) สถานการณ์ทางด้านเศรษฐกิจสังคมการเกษตร 4) ต้นทุนการผลิตและราคาสินค้า 5) กระบวนการเพาะปลูกและการเพิ่มมูลค่าผลผลิตทางการเกษตร และ 6) การสนับสนุนจากสถาบันและองค์การที่เกี่ยวข้อง ส่งต่อให้เกษตรกรกลุ่มตัวอย่างที่ประกอบอาชีพเพาะปลูกข้าว 3 ภูมิภาค 3 จังหวัด ที่มีพื้นที่เพาะปลูกข้าวสูงสุด จำนวน 120 คน หลังจากนั้นดำเนินการประเมินผลการนำสารสนเทศที่ได้รับไปใช้ประโยชน์ ซึ่งแบ่งช่วงการประเมิน 3 สัปดาห์ ประเมิน 1 ครั้ง รวมระยะเวลาการทดลองรับสารสนเทศการเกษตร 3 เดือน และประเมินผลการนำไปใช้ประโยชน์รวม 4 ครั้ง พร้อมดำเนินการสนทนากลุ่มเพื่อยืนยันรูปแบบและหาแนวทางการพัฒนารูปแบบการจัดการสารสนเทศการเกษตร เครื่องมือที่ใช้ในการวิจัยประกอบด้วย แบบประเมินการใช้ประโยชน์ และคำถามการสนทนากลุ่ม ผลจากการวิจัยสามารถนำเสนอได้ 2 ประการ คือ 1) ผลการใช้รูปแบบการจัดการสารสนเทศการเกษตร พบว่า เกษตรกรที่ได้รับสารสนเทศสามารถใช้ประโยชน์จากสารสนเทศในการวางแผนการเพาะปลูก การลดต้นทุนการผลิต การเก็บเกี่ยว การจัดจำหน่าย และการแปรรูปผลผลิตเพื่อสร้างมูลค่าเพิ่มได้ผลเป็นอย่างดี 2) รูปแบบการจัดการสารสนเทศการเกษตรได้รับการยืนยันจากผู้เชี่ยวชาญด้านการจัดการสารสนเทศการเกษตร ผู้เชี่ยวชาญด้านการพัฒนาระบบสื่อสารดิจิทัล และเกษตรกรที่ทดลองรับสารสนเทศการเกษตร โดยสามารถนำแนวทางไปประยุกต์ใช้ในการจัดการสารสนเทศการเกษตร เพื่อพัฒนาศูนย์ประมวลข้อมูลการเกษตรได้ต่อไป คำสำคัญ: การจัดการสารสนเทศ, สารสนเทศการเกษตร, โมเดลรูปแบบ   This action research aimed at studying the use of agricultural information management and searching for the development pathway of information management for agriculturalists. The author followed the designed pattern of information management and worked as the data processing center to gather weekly agricultural information from every region then processed the information via the synthesized analysis in to 6 principles of agricultural information as follows: 1) environment affecting the growing 2) state’s policy 3) economic, social, and agricultural situations 4) production cost and product price 5) growing process and value adding of agricultural products and 6) supports from related institutions and organizations. These have been transferred to the sample group that is 120 agriculturalists from 3 provinces of 3 regions each, who possess the largest rice farming. After the evaluation of the operation, the duration of evaluation is every 3 weeks for one evaluation which longed 3 months and there are 4 results of the information management. Moreover, the research included the focus group to confirm the use of management pattern and development pathway of agricultural information management. The researching tools consisted of the evaluation and questions in the focus group. According to the research, it could be demonstrated into 2 sections as follows: 1) the result from the use of agricultural information management, it was found that the agriculturalists are able to receive the benefits from the information for planning their farming, cost reduction, harvest, distribution, and processing of products to increase values. 2) The pattern of agricultural information management has been guaranteed by the experts in agricultural information management, in digital communication system development, and the agriculturalists who participated in the experiment. The pathway could be applied in agricultural information management in order to develop the agricultural data process center in the future. Keywords: information management, agricultural information, pattern model